Effects of graphene content and dry density on swelling pressure of graphene-modified GMZ bentonite. (1st August 2022) - Chen, Yong-Gui; Zhang, Xiao-Xiao; Liu, Xue-Min; Ye, Wei-Min; Wang, Qiong
Highlights: Swelling pressure reduced as graphene content increased. Swelling pressure increased as dry density increased. A prediction model for swelling pressure was proposed. Correlated with microstructure and pore structure changes due to swelling pressure. Abstract: Compacted bentonite has been widely used as buffer material in the deep geological disposal of high-level radioactive waste because of its physical and chemical characteristics, such as its swelling property, which plays a crucial role in the safe operation of repositories. To enhance the properties of bentonite as buffer material, graphene has been used to modify pure bentonite. In this study, the swelling pressure of graphene-modified GMZ bentonite (GMB) was measured under different conditions to investigate the effect of the graphene content and dry density on the swelling properties of modified bentonite. The swelling pressure curve exhibits a "double-peak" pattern, which fades with the increase in the graphene content from 0% to 6% and decrease in the dry density from 1.8 to 1.6 g/cm 3 . The microstructure of GMB were analyzed under various conditions using mercury intrusion porosimetry and scanning electron microscopy. Results show that, in contrast to intra-aggregate pores (micropores), the distribution of inter-aggregate pores (macropores) is greatly affected by the graphene content and dry density. Based on the results, the swelling pressure of GMB under different conditions can be predicted with a logarithmic function. The present work can provide a reference for the design of GMB as buffer/backfill materials for deep geological disposal.